KESIAPAN STAIN PAMEKASAN DALAM MENYELENGGARAKAN PROGRAM MAGISTER MANAJEMEN PENDIDIKAN ISLAM - Mohammad Qosim (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
This article describes STAIN Pamekasan readiness in organizing Islamic education master program especially the lecturer, literatures, infrastructure, prospect students, and curriculum. Data and findings showed that lecturer, literatures, infrastructure, prospect students, and curriculum conceptually ready in organizing Islamic Education Management master program.